Demographic and clinical predictors of gestational diabetes mellitus in early pregnancy: a prospective observational study - Agarwal, Pooja; Thakur, Nisha; Agrawal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Gestational diabetes mellitus (GDM) poses significant health risks to both the mother and fetus. Identifying predictors of GDM early in pregnancy can facilitate timely intervention and reduce associated morbidity. To evaluate demographic and clinical parameters as predictors of GDM in pregnant women attending antenatal care before 20 weeks of gestation. Methods: A prospective observational study was conducted on 200 pregnant women attending antenatal outpatient department at J.L.N. Hospital and Research Centre, Bhilai, Chhattisgarh. Relevant demographic and clinical data were recorded. DIPSI tests were conducted at <20 weeks, 24-28 weeks and 32-34 weeks of gestation. Associations between GDM and factors such as age, BMI, family history of diabetes, gravidity, haemoglobin and socioeconomic status were analysed using chi-square and t-tests. Results: GDM was diagnosed in 34 participants (17%). Significant predictors of GDM included advanced maternal age (p<0.01), higher BMI (p=0.02) and positive family history of diabetes (p<0.001). Gravidity, hemoglobin and socioeconomic status did not show any associations. Conclusions: Maternal age, BMI and family history of diabetes are strong predictors of GDM. Routine screening and early risk stratification based on these predictors can guide targeted interventions, particularly in resource-limited settings.